A concepção dialógica e as políticas universitárias extensionistas na Universidade Federal de Goiás - Félix, Murilo Emos (2023)
University extension as one of the pillars of universities plays a fundamental role in the pedagogical process of undergraduates and society, while serving as an effective method of sharing science and popular knowledge. However, since the period of redemocratization of the country and re-signification of the State and of education, based on Paulo Freire's thought, university extension not only communicates and disseminates science, but occurs in attention to the dialogic principle in an attempt to overcome the welfare conception . In the sense of dialogue, the university promotes a qualified interaction through the exchange of knowledge, no longer just providing one-way information. In this context, in 2014, as provided for in the National Education Plan, the mandatory inclusion of at least 10% of the undergraduate curriculum dedicated exclusively to extension. The research surveys how the Federal University of Goiás politically develops extension. As for the curricular insertion process, the research elaborated a questionnaire applied to the professors of the Campus Goiás of the UFG, as well as used the database supplied by the Pro-Rectory of Extension and Culture of the UFG. Inferences were drawn from both instruments as to the perspectives of extension up to this stage of implementation of the curricularization, among the main ones we can mention: the positive reception of the curricularization process and the difficulty of redoing the curricula . The investigation involves the analysis of the UFG's Institutional Development Plans (PDI's) and other institutional documents such as the Management Plan and the Pedagogical Political Projects of the Courses. Finally, the research produced a diagnosis on university extension at UFG, with the main conclusions being the finding of a fragmented policy for extension in the sense of a preponderance of actions developed for convenience. On the other hand, the curricularization process must change this situation with the inclusion of actions in the PPC's, making them officially part of the course policy